Walter Block and Reflections on Libertarian Arguments for Free Market - Mazur, Karol (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
The article shows the attitude of freedom movement towards problem of implementation and realization of libertarian rules in nowadays world. The article shows the perspectives of two rather different attitudes that exist in contemporary freedom movement. It pictures two freedom traditions that come from one common ideological base, and whose development and praxis have led to various mutually exclusive conclusions. For the need of article the two perspectives are called “legalists” and “revolutionists”. Both see the necessity of realization of libertarian assumptions in completely different ways. After describing their ideological postulates the article centers on picturing the main problems that are reason of such a vibrant dispute among the two sides. The conclusions help to understand why only one of discriminated options is far closer to realize its postulates. The article considers thoughts of Walter Block, Hans-Herman Hoppe, Murray Rothbard and Edward Konkin III.